Desain Sistem E-Assessment Pada Pembelajaran Fisika di LPTK - Hairunnisyah Sahidu; Gunawan Gunawan; Indriaturrahmi Indriaturrahmi; Fitri Astutik (Department of Physics Education, Universitas Mataram, 2017)
Computer technology can be used in learning assessment activities, commonly called e-assessment. Assessment is an important part of learning. This study aims to develop an e-assessment model using Leraning management System (LMS) based on Moodle. This development research uses DDD-E model, including decision, design, develop and evaluate. Development of e-assesement using Moodle 3.3 software. This model produces e-assessment products that can be accessed online and can help learners in evaluating their learning outcomes independently. In addition, this model also encourages motivation and problem solving in the given lesson.